Anti-thermal-quenching red-emitting GdNbO4:Pr3+ phosphor based on metal-to-metal charge transfer for optical thermometry application. Issue 42 (19th October 2021) - Ye, Wanggui; Ma, Chaoyang; Li, Yanbin; Zhao, Chong; Wang, Yuzhen; Zuo, Chuandong; Wen, Zicheng; Li, Yingkui; Yuan, Xuanyi; Cao, Yongge
Abstract : An anti-thermal quenching strategy is proposed to develop GdNbO4 :Pr 3+ red phosphor, which is a promising candidate for the high-performance optical temperature sensing with increasing red emission intensity during the heating process. Abstract : The thermal quenching of phosphors seems to be inevitable, which severely limits their applications related to high temperature. Therefore, the development of thermally stable phosphors and the exploration of anti-thermal quenching mechanism is still a pivotal need. Herein, an internal self-regulation anti-thermal quenching strategy has been proposed to develop Pr 3+ -activated GdNbO4 red phosphor, whose loss of red emission intensity can be compensated at the expense of blue emission during the heating process. The integrated photoluminescence intensity of GdNbO4 : x %Pr 3+ ( x = 0.1–2.5) is maintained or even continuously enhanced from 300 K to 620 K based on the metal-to-metal charge transfer between Pr 3+ ions and Nb 5+ ions. For the GdNbO4 :0.1%Pr 3+ sample, the integrated intensity of its red emission remarkably reaches 290% at 540 K compared to that at 300 K. As expected, the opposite temperature response of Pr 3+ 3 P0 → 3 H4 and 1 D2 → 3 H4 indicates that GdNbO4 :0.1%Pr 3+ has advantage in optical thermometry based on MMCT ( S r = 0.7% K −1 at 430 K and S a = 18% K −1 at 620 K). Our work could open a new gateway to design phosphors with anti-thermal quenching performance for high-temperature applications and develop high-performance optical temperature sensing in Pr 3+ -activated oxide phosphors.